Antiphospholipid Syndrome Recent Advances in Clinical and Basic Aspects - Žigon, Polona (IntechOpen, 2022)
Antiphospholipid syndrome (APS) is an acquired autoimmune disorder in which the immune system mistakenly produces antiphospholipid antibodies that attack tissues in the body. These antibodies can lead to the formation of blood clots in arteries and veins. During pregnancy, APS can also lead to miscarriage and stillbirth. Classification criteria require a clinical event (i.e., thrombosis or pregnancy complication) and persistent positive blood test results at least three months apart that detect lupus anticoagulant, anti-cardiolipin antibodies, or anti-β2-glycoprotein-1 antibodies. This book addresses important clinical aspects of APS, including stroke and APS, obstetric manifestations of APS, and bleeding complications in APS. It also discusses the diagnostic utility of a novel autoantibody against β2-glycoprotein I/HLA class II complexes as a promising biomarker for APS. Finally, this book also reviews the latest findings in the field of extracellular vesicles in APS and provides explanations of their role in the pathogenesis of APS.